Diagnostic Laparoscopy in Patients With Peritoneal Carcinomatosis Is Safe and Does Not Delay Cytoreductive Surgery With Hyperthermic Intraperitoneal Chemotherapy. Issue 4 (April 2022) - Hanna, David N.; Ghani, Muhammad O.; Hermina, Andrew; Mina, Alexander; Bailey, Christina E.; Idrees, Kamran; Magge, Deepa
Background: Outcomes of cytoreductive surgery with hyperthermic intraperitoneal chemotherapy (CRS-HIPEC) among patients with peritoneal carcinomatosis (PC) depend largely on the extent of peritoneal disease. Since PC is not reliably evaluated with cross-sectional imaging, tumor burden is often evaluated with diagnostic laparoscopy (DLS). The aims of this study are to evaluate the safety of DLS in patients with peritoneal disease and determine if DLS delays time to CRS-HIPEC. Methods: We performed an institutional retrospective review of 145 patients who underwent CRS-HIPEC between 2013 and 2020. Patients were divided into 2 groups: those who underwent an electively scheduled DLS prior to CRS-HIPEC and those who did not. Intraoperative and postoperative complications associated with DLS were determined from the surgeon's operative report. Time from diagnosis of PC to CRS-HIPEC was compared between the 2 groups. Results: Of the 145 patients available for analysis, 47% (68) underwent DLS and 44% (64) did not. Of all the diagnostic laparoscopies performed, there was 1 (1.5%) intraoperative complication. The duration between diagnosis of peritoneal carcinomatosis and surgery was 4.9 months among patients who underwent DLS prior to CRS-HIPEC and 4.3 months among patients who did not ( P = .79). Conclusion: In this retrospective analysis, diagnostic laparoscopy prior to CRS-HIPEC demonstrated a comparable rate of DLS-associated complications compared to other gastrointestinal malignancies and does not prolong time from diagnosis to CRS-HIPEC. Thus, in patients undergoing evaluation for CRS-HIPEC, diagnostic laparoscopy provides significant value in patient selection without incurring perioperative risk or delay in CRS-HIPEC.